Climatological analysis of persistent, extreme and broad rainfall cases between 1986-2016 in Santa Catarina, Brasil - Prieto, Raidel Báez; Oliveira, Francisco Henrique de; Teixeira, Mateus da Silva (Ciência e Natura, 2020)
In a better qualified society, in search of sustainable cities, it is important to study and know the extreme and recurrent natural phenomena. Extreme rain, as an example of atmospheric phenomena, causes several and negative impacts on Society, leaving clear signs of the areas most susceptible to disasters. Considering researchs of climatology in Santa Catarina State (SC), as well as the use of applied statistics, the main objective in this research is to study the extreme events of persistent and broad rainfall in the cities of SC between 1986-2016. The results show that the regions that most suffer with high frequency and intensity of this type of phenomenon are more on the coast like Florianópolis and Itajaí. In the other hand, in the last 30 years, the west cities of SC present a decrease in the trend, in the quantity of events and of your total accumulated.